Results of a prospective phase 2 study of pazopanib in patients with surgically unresectable or metastatic chondrosarcoma. Issue 1 (11th September 2019) - Chow, Warren; Frankel, Paul; Ruel, Chris; Araujo, Dejka M.; Milhem, Mohammed; Okuno, Scott; Hartner, Lee; Undevia, Samir; Staddon, Arthur
Abstract : Background: This single‐arm, multicenter, phase 2 study evaluated the safety and antitumor activity of pazopanib in patients with unresectable or metastatic conventional chondrosarcoma. Methods: Eligible patients had conventional chondrosarcoma of any grade with measurable tumors that were unresectable or metastatic. Patients with mesenchymal, dedifferentiated, and extraskeletal myxoid chondrosarcoma subtypes and patients who received prior tyrosine kinase inhibitor therapy were excluded. Pazopanib at 800 mg once daily was administered for 28‐day cycles. Tumor responses were evaluated by local radiology assessments every 2 cycles. The primary endpoint was the disease control rate (DCR) at week 16 (4 cycles). Results: Forty‐seven patients were enrolled. The DCR at 16 weeks was 43% (95% confidence interval [CI], 28%‐58%), which was superior to the null hypothesis rate of 30%, but the 2‐sided P value (exact test) was .09 (1‐sided P  = .045). One patient had a partial response. The median overall survival was 17.6 months (95% CI, 11.3‐35.0 months), and the median progression‐free survival was 7.9 months (95% CI, 3.7‐12.6 months). Grade 3 or higher adverse events were infrequent; hypertension (26%) and elevated alanine aminotransferase (9%) were most common. Conclusions: This study provides evidence of positive drug activity for pazopanib in conventional chondrosarcoma. Abstract : This single‐arm, multicenter, phase 2 study evaluates the safety and antitumor activity of pazopanib in patients with unresectable or metastatic conventional chondrosarcoma. This study provides evidence of positive drug activity for pazopanib in conventional chondrosarcoma.